Aquatic macroinvertebrate image dataset - Koen, R. C. J.; Koen, F. J. K. (2023)
Dataset contains approximately one thousand images of each of the thirteen mini stream assessment scoring system (miniSASS) aquatic macroinvertebrate groups. The dataset comprises approximately thirteen thousand photos.